DISINFEKSI UNTUK PROSES PENGOLAHAN AIR MINUM - Said, Nusa Idaman (Jurnal Air Indonesia, 2007)
Water disinfection means the removal, deactivation or killing of pathogenic microorganisms. Microorganisms are destroyed or deactivated, resulting in termination of growth and reproduction. When microorganisms are not removed from drinking water, drinking water usage will cause people to fall ill. Chemical inactivation of microbiological contamination in natural or untreated water is usually one of the final steps to reduce pathogenic microorganisms in drinking water. Combinations of water purification steps (oxidation, coagulation, settling, disinfection, and filtration) cause (drinking) water to be safe after production. As an extra measure many countries apply a second disinfection step at the end of the water purification process, in order to protect the water from microbiological contamination in the water distribution system. Usually one uses a different kind of disinfectant from the one earlier in the process, during this disinfection process. The secondary disinfection makes sure that bacteria will not multiply in the water during distribution. This paper describes several technique of disinfection process for drinking water treatment. Disinfection can be attained by means of physical or chemical disinfectants. The agents also remove organic contaminants from water, which serve as nutrients or shelters for microorganisms. Disinfectants should not only kill microorganisms. Disinfectants must also have a residual effect, which means that they remain active in the water after disinfection. For chemical disinfection of water the following disinfectants can be used such as Chlorine (Cl2), Hypo chlorite (OCl-), Chloramines, Chlorine dioxide (ClO2), Ozone (O3), Hydrogen peroxide etch. For physical disinfection of water the following disinfectants can be used is Ultraviolet light (UV). Every technique has its specific advantages and and disadvantages its own application area sucs as environmentally friendly, disinfection byproducts, effectivity, investment, operational costs etc. Kata Kunci : Disinfeksi, bakteria, virus, air minum, khlor, hip khlorit, khloramine, khlor dioksida, ozon, UV.